Sex-specific associations of prenatal Chinese famine exposure with cataract risk at age sixty: a cross-sectional study - Yuanyou Xia; Xiaoyang Xu; Siyao Wang (BMC Women's Health)
Abstract Background Age-related cataract (ARC) is among the most common blinding eye disorders among the elderly. Prenatal nutrition may cause irreversible damage to the development of the ocular crystalline lens. Nevertheless, the potential association between prenatal malnutrition and age-related cataract has not been thoroughly examined. We investigated the prevalence of cataract at the age of 60 after prenatal exposure to Chinese famine (1959–1961) and particularly evaluated whether there was a disparity in this effect between men and women. Methods We utilized the health examination medical record system of a large-scale comprehensive hospital to screen individuals born in Chongqing, China and undergoing eye health examinations. Participants were categorized based on their year of birth into the famine-exposed group (1960) and the non-exposed group (1963), with their medical records at age 60 extracted from the database. Univariate and multivariate logistic regression analyses were conducted to investigate the association between famine exposure and the risk of developing ARC by age 60. Results The prevalence of ARC was significantly higher in the famine-exposed group (60.26%) compared to the non-exposed group (47.90%) (P < 0.001). After adjusting for diabetes history, body mass index (BMI), fasting blood glucose (FBG) level, and high-density lipoprotein (HDL) level using multivariate logistic regression analysis, the risk of ARC remained significantly higher in the famine-exposed group (OR:1.63; 95%CI:1.31–2.03). Subgroup analysis by sex indicated that women exposed to famine (OR: 1.77; 95% CI: 1.25–2.52) exhibited a higher risk of ARC compared to men (OR: 1.53; 95% CI: 1.16–2.03). Conclusions Prenatal exposure to famine might increase the risk of ARC among Chinese adults at age 60, and women exhibit a higher susceptibility than men.